Nutrition of primary school children: world and Ukrainian realities - Vatan, M.; Babienko, V.; Levkovska , V. (Journal of Education, Health and Sport, 2021)
The aim of the study is to assess the actual nutrition of primary school children in Ukraine and other countries. Material and methods. An analysis of publications in scientific journals and reports of national agencies on the state of nutrition of primary school children. Search depth 10 years. The following search strategy "primary school", "nutrition", "sentinel surveillance" was used. The 15 most relevant publications were selected for further analysis. In addition, a survey of 450 primary school students was conducted on the quality of nutrition during school. Statistical processing was performed using MedCalc software. Results. Most countries in the world have some kind of nutrition program for younger students. At the same time, the diets that these programs offer do not always meet the principles of healthy eating. According to our own data, only 96 (21.3%) of the surveyed schoolchildren aged 6-10 had a full meal at school. For the rest, there was either a qualitative or quantitative discrepancy in the composition of breakfast and lunch at school. The children noted the lack of time for meals, low taste of school lunches. Every second child consumed insufficient volume of fluids during school. Conclusion. The nutritional status of primary school children is affected by lack of time for eating and recreational physical activity, unbalanced diet when using home lunch boxes and low coverage of high school students with organized meals. Unlike other countries, the main problem for Ukraine is not an energy surplus diet, but the popularity of fast food among children of primary school age is undoubtedly unacceptable.